Age-related changes in dynamic moduli of ovine vitreous. (January 2015) - Colter, Jourdan; Williams, Alex; Moran, Patrick; Coats, Brittany
Abstract: Multiple rheological studies have characterized the dynamic material properties of adult vitreous, but no studies have investigated vitreous properties in the immature eye. In this study, premature, infant and adult ovine vitreous specimens were tested in shear to identify differences in dynamic moduli with age. Significant inertial artifact and rapid degradation of the vitreous ex vivo hindered the ability to accurately collect dynamic data through standard oscillation protocols. Therefore, dynamic moduli were calculated by converting relaxation spectrum data to the retardation spectrum, resulting in the calculation of the storage ( G ′) and loss ( G ″) moduli from the first few milliseconds of creep testing when tissue degradation and inertia is minimal. The technique was validated against two synthetic materials that span the viscoelastic spectrum. G ′ and G ″ of the primarily viscous synthetic material (polystyrene, tan δ =0.61) and G ′ of the primarily elastic material (agar, tan δ =0.06) were not significantly different than those calculated from dynamic oscillatory testing ( p <0.05). G ″ of agar was overestimated (4–39%) with the interconversion technique due to creep ringing. Ovine vitreous was primarily viscous (tan δ =1.31), so this technique was used to evaluate changes in dynamic moduli with age. G ′ and G ″ for adult vitreous was 2–4 times and 1.5–2 times lower, respectively, than infant vitreous, corresponding to the structural breakdown of the vitreous with age. The dynamic moduli of premature vitreous was lower than infant and adult, likely due to premature development of the vitreal structure. These data suggest that significant differences exist between the viscoelastic response of infant and adult vitreous, and computational models of the pediatric eye will require appropriate age and rate material properties of vitreous. Highlights: Vitreous degrades within minutes ex vivo. Spectrum interconversion allowed high frequency data from first msec of testing. Pediatric vitreous had higher dynamic moduli than adult vitreous. Premature vitreous had lower dynamic moduli than both adult and infant. Age-related findings correlate with integrity of collagen/hyaluronan in vitreous.